Method for improving corrosion resistance of magnesium alloy laser welding joint

By adding potassium fluorozirconate to the electrolyte of the magnesium alloy laser welding joint and using argon double-sided circulation during the welding process, nanozirconia phase particles were generated, which solved the problem of poor corrosion resistance of the magnesium alloy laser welding joint, and significantly improved its corrosion resistance and service life.

CN119635195AActive Publication Date: 2025-03-18WENZHOU SPECIAL EQUIP TESTING SCI RES INST (WENZHOU SPECIAL EQUIP EMERGENCY RESPONSE CENT) +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411866726.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-18
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

Magnesium alloys are prone to oxidation during laser welding, resulting in poor corrosion resistance of welded joints, affecting their application range.

Method used

Potassium fluorozirconate is added to the silicate electrolyte, and the double-sided circulation of argon is achieved through homemade fixtures to generate nanozirconia phase fine particles, thereby improving the corrosion resistance of magnesium alloy laser welding joints.

Benefits of technology

The corrosion resistance of magnesium alloy laser welding joints is significantly improved, the defects of zirconia nanoparticles in the microarc oxide film layer are reduced, and the service life of magnesium alloy laser welding products is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119635195A_ABST
    Figure CN119635195A_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving corrosion resistance of a magnesium alloy laser welding joint, which is applied to manufacturing of a magnesium alloy laser welding product and comprises the following steps: S1, linearly cutting a material; s2, pretreatment is conducted, specifically, the cut magnesium alloy base plate is polished step by step through SiC abrasive paper, and a surface oxidation film is removed; s3, assembling before welding, wherein the pretreated magnesium alloy base plate is fixed to a clamp; s4, welding is conducted, specifically, the clamp where the magnesium alloy base plate to be welded is fixed is placed on a workbench of a laser welding machine, welding is conducted after laser welding parameters are set, and after treatment, cleaning is conducted through an ultrasonic cleaning machine and blow-drying is conducted; and S5, micro-arc oxidation: putting the prepared improved electrolyte into a stainless steel tank, then carrying out micro-arc oxidation treatment by adopting micro-arc oxidation power supply equipment, washing with distilled water after the treatment is finished, and blow-drying. According to the method, the micro-arc oxidation process method and the electrolyte are improved, the method is mainly suitable for improving the corrosion resistance of a magnesium alloy laser welding joint, and the service life of a magnesium alloy laser welding product is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of magnesium alloy welding, and in particular to a method for improving the corrosion resistance of magnesium alloy laser welded joints. Background Art

[0002] Magnesium alloy is the lightest metal material in the world. It is widely used in aerospace, large ships, computer devices and sports equipment. It has the characteristics of low density, high specific strength and large elastic modulus, which can achieve the goal of lightweight. In view of the current energy-saving and environmental protection background, reducing weight as much as possible can achieve the goal of energy saving and environmental protection. The corrosion resistance of materials is a major performance evaluation index that the engineering community is currently concerned about. However, due to the high chemical activity and poor corrosion resistance of magnesium alloys, the application scope of magnesium alloys is seriously restricted. The poor corrosion resistance of magnesium alloys has become a concern of the industry. In the engineering application process of magnesium alloys, welding of workpieces is inevitable. During the welding process, due to the interaction between the laser and the magnesium alloy sheet, magnesium alloys are prone to oxidation, which will inevitably deteriorate the performance of magnesium alloy laser welding joints. The composition and microstructure of the material jointly determine the corrosion performance of the material. During the welding process, the material undergoes a very complex thermodynamic process, during which the performance of the material is greatly affected. Laser welding is a melting welding technology. Due to the complex thermal movement during the welding process, pores, inclusions and uneven structure will be generated. In addition, oxidation during the welding process will seriously affect the performance of the laser welded joint, making the performance of the joint area worse than that of the parent material.

[0003] Micro-arc oxidation technology is a method that generates plasma spark discharge points on the metal surface by applying high voltage to the workpiece, thereby generating a dense oxide film, so that the corrosion resistance of the workpiece is significantly improved. However, in the process of micro-arc oxidation reaction of magnesium alloy welding workpieces, the complex physical and chemical reactions of micro-arc oxidation will cause many defects in the micro-arc oxidation film layer, such as pores and thermal cracks. The corrosion resistance of magnesium alloy laser welding joints is improved by adding zirconium oxide nanoparticles, but the artificial addition of zirconium oxide nanoparticles often makes the phase interface in the micro-arc oxidation film layer unclean. During the micro-arc oxidation reaction, a large amount of thermal stress is generated, which will lead to stress concentration at the phase interface, and failure occurs first and cracks are generated. Therefore, in view of the above situation, the present application has developed a method for further improving the corrosion resistance of magnesium alloy laser welding joints by adding potassium fluorozirconate to a silicate electrolyte, which is applied to magnesium alloy welding structures. Summary of the invention

[0004] The purpose of the present invention is to provide a method for improving the corrosion resistance of magnesium alloy laser welded joints. The two-sided circulation of argon gas is achieved through a homemade fixture to prevent the magnesium alloy workpiece from being oxidized during the welding process and affecting the joint performance as much as possible. Potassium fluorozirconate is added to the electrolyte, and the micro-arc oxidation film layer generated on the surface of the magnesium alloy contains nano-zirconium oxide phase particles, which is beneficial to improving the corrosion resistance of magnesium alloy laser welded joints. The method is mainly suitable for improving the corrosion resistance of magnesium alloy laser welded joints and extending the service life of magnesium alloy laser welded products.

[0005] To achieve the above object, the present invention provides a method for improving the corrosion resistance of magnesium alloy laser welded joints, which is applied to the manufacture of magnesium alloy laser welded products, and comprises the following steps:

[0006] S1: Wire cutting material: Use a wire cutting machine to cut the magnesium alloy sheet into the required size to form a flat magnesium alloy substrate to be welded;

[0007] S2: Pretreatment: The cut magnesium alloy substrate is polished step by step with SiC sandpaper to remove the surface oxide film, and then cleaned and degreased, and then dried and bagged for storage;

[0008] S3: Assembly before welding: Fix the pre-treated magnesium alloy substrate on the fixture to ensure that the weld is flush with the shielding gas channel on the fixture;

[0009] S4: Welding: Place the fixture that fixes the magnesium alloy substrate to be welded on the workbench of the laser welding machine, set the laser welding parameters, align the laser beam with the weld, and weld. After processing, clean it with an ultrasonic cleaner and blow dry it;

[0010] S5: Micro-arc oxidation: The prepared electrolyte is placed in a stainless steel tank, which serves as the cathode. The magnesium alloy plate after laser welding is also placed in the electrolyte as the anode. Then, a micro-arc oxidation power supply device is used for micro-arc oxidation treatment. After the treatment, it is rinsed with distilled water and blown dry.

[0011] The electrolyte is an aqueous solution composed of a uniform mixture of sodium silicate, sodium hydroxide, potassium fluorozirconate and deionized water.

[0012] According to an embodiment of the present application, the clamp includes a clamp base and a fixing component. A groove-shaped protective gas channel is opened in the middle of the clamp base, and an open groove is opened in the protective gas channel at the center line of the clamp base; the fixing component includes a mounting groove and a connecting rod. The upper and lower ends of the opening groove are both laterally provided with mounting grooves, and the left and right sides of the opening groove are provided with longitudinal connecting rods, and the two ends of the connecting rod are respectively fixed on the mounting grooves on the upper and lower sides.

[0013] According to an embodiment of the present application, step S3 specifically includes: the two magnesium alloy substrates to be welded are spliced ​​together at the welding point to form a weld, the weld is placed along the open groove so that the back of the weld is located at the opening of the protective gas channel, and the magnesium alloy substrates on both sides of the weld are pressed and fixed by connecting rods, and the two ends of the connecting rods are fixed in the installation grooves by bolts.

[0014] According to an embodiment of the present application, step S2 further specifically includes: SiC sandpaper step-by-step polishing is performed using 400#-2000# sandpaper to remove the surface oxide film, the polished magnesium alloy substrate is rinsed with deionized water, then placed in an acetone solution and ultrasonically cleaned to remove oil, and then dried and bagged for storage.

[0015] According to an embodiment of the present application, the laser welding parameters in step S4 are: laser power 800-1200W, welding speed 25-35mm / s, defocus amount 0-5mm, the weld is protected on both sides by argon gas, the front argon gas flow rate is 20-22.5L / min, and the back argon gas flow rate is the same as the front argon gas flow rate.

[0016] According to an embodiment of the present application, the preparation of the electrolyte in step S5 includes the following specific steps:

[0017] S51: First, place corresponding amounts of sodium silicate and sodium hydroxide in a beaker, stir magnetically, and fully dissolve;

[0018] S52: Place the corresponding amount of potassium fluorozirconate in another beaker, add deionized water to dissolve, heat to 50° C., stir magnetically, and fully dissolve;

[0019] S53: pouring the dissolved potassium fluorozirconate solution into the prepared sodium silicate and sodium hydroxide solutions, stirring sufficiently and reacting completely to obtain a milky white colloidal solution;

[0020] S54: diluting the prepared milky white colloidal solution to a corresponding electrolyte volume and pouring it into a stainless steel tank for use;

[0021] Among them, the mass ratio of sodium silicate, sodium hydroxide, potassium fluorozirconate and deionized water is 6:1:2:500.

[0022] According to an embodiment of the present application, the electrolysis parameters in the micro-arc oxidation treatment in step S5 are: using a constant voltage mode, a positive voltage of 300V-500V, a negative voltage of 0V-30V, a duty cycle of 10-30%, a power frequency of 300-800Hz, and an oxidation time of 5-30min.

[0023] According to an embodiment of the present application, the power supply equipment for the micro-arc oxidation treatment in step S5 is a FL7-MAO30G micro-arc oxidation power supply equipment.

[0024] According to an embodiment of the present application, the temperature of the electrolyte during the micro-arc oxidation treatment is between 40-50°C.

[0025] According to an embodiment of the present application, the micro-arc oxidation film layer formed in the micro-arc oxidation treatment process contains nano-zirconium oxide phase particles.

[0026] The beneficial effects of the technical solution of the present invention compared with the prior art are:

[0027] 1. The present invention adopts micro-arc oxidation technology to produce zirconium oxide nanoparticles for magnesium alloy welded joint products, inhibits the expansion of film cracks, overcomes the defects of pores and thermal cracks generated in the conventional micro-arc oxidation process, and further improves the corrosion resistance of magnesium alloy laser welded joints.

[0028] 2. The present invention adopts the technology of micro-arc oxidation in an electrolyte added with potassium fluorozirconate. The micro-arc oxidation film layer generated on the surface of the magnesium alloy contains nano zirconium oxide phase particles, which is beneficial to improving the corrosion resistance of magnesium alloy laser welding joints. Zirconium oxide nanoparticles are produced by chemical reactions. Compared with artificially added zirconium oxide nanoparticles, their phase interface is relatively clean and not easy to produce stress concentration due to impurities in the interface. Cracks are preferentially generated at the phase interface. This method applies potassium fluorozirconate to the welded joint, which reduces the cracks at the joint, so its corrosion resistance is significantly improved.

[0029] 3. During the welding process, the present invention sets a self-made fixture so that the weld is located at the opening of the protective gas channel, and argon gas is introduced into the protective gas channel to achieve double-sided flow of argon gas in the weld area, thereby preventing the magnesium alloy workpiece from being oxidized during the welding process and affecting the joint performance as much as possible. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 A schematic diagram of the structure of a clamp in an example of the present invention;

[0031] Figure 2 This is a polarization curve diagram of a magnesium alloy welded joint product in an example of the present invention;

[0032] Figure 3 This is an impedance spectrum of a magnesium alloy welded joint product in an example of the present invention;

[0033] Figure 4 This is a SEM image of Weld-MAO processed by composite micro-arc oxidation of magnesium alloy welded joints in an example of the present invention;

[0034] Figure 5 This is a SEM image of Weld-MAO-Zr, a magnesium alloy weld joint treated with composite micro-arc oxidation after adding zirconate in an example of the present invention.

[0035] The following are the descriptions of the reference numerals:

[0036] 1. magnesium alloy substrate, 2. laser beam, 3. weld, 10. fixture base, 11. protective gas channel, 21. connecting rod, 22. mounting groove, 111. opening groove. DETAILED DESCRIPTION

[0037] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. The following embodiments are used to illustrate the present invention, but are not intended to limit the scope of the present invention.

[0038] The present application discloses a whole process for improving the corrosion resistance of magnesium alloy laser welded joints, comprising the following steps:

[0039] S1: Wire cutting material: Use a wire cutting machine to cut the magnesium alloy sheet into required specifications and sizes to form a flat magnesium alloy substrate 1 to be welded;

[0040] Specifically, a magnesium alloy plate (AZ31, AZ31B, AZ91, AZ91D) of 100 mm×100 mm×2 mm was cut into a welding pattern of 25 mm×50 mm×2 mm using a wire cutting machine.

[0041] S2: Pretreatment: The cut magnesium alloy substrate 1 is polished step by step with SiC sandpaper to remove the surface oxide film, and then cleaned and degreased, and then dried and bagged for storage;

[0042] Specifically, step S2 also specifically includes: SiC sandpaper step-by-step polishing is to use 400#-2000# sandpaper to polish step by step to remove the surface oxide film, the polished magnesium alloy substrate 1 is rinsed with deionized water, then placed in acetone solution for ultrasonic cleaning and degreasing, and then dried and bagged for storage.

[0043] S3: Assembly before welding: Fix the pre-treated magnesium alloy substrate 1 on the fixture to ensure that the weld 3 is flush with the shielding gas channel 11 on the fixture;

[0044] Specifically, Figure 1 As shown, the clamp includes a clamp base 10 and a fixing assembly. A groove-shaped protective gas channel 11 is opened in the middle of the clamp base 10, and an open groove 111 is opened in the protective gas channel 11 at the center line of the clamp base 10; the fixing assembly includes a mounting groove 22 and a connecting rod 21. The upper and lower ends of the opening groove 111 are both laterally provided with mounting grooves 22, and the left and right sides of the opening groove 111 are provided with longitudinal connecting rods 21, and the two ends of the connecting rod 21 are respectively fixed on the mounting grooves 22 on the upper and lower sides.

[0045] Specifically, step S3 further specifically includes: the two magnesium alloy substrates 1 to be welded are spliced ​​together at the welding position to form a weld 3, the weld 3 is placed along the opening groove 111, so that the back of the weld 3 is located at the opening of the protective gas channel 11, the magnesium alloy substrates 1 on both sides of the weld 3 are respectively pressed and fixed by connecting rods 21, and the two ends of the connecting rod 21 are fixed in the mounting groove 22 by bolts, so that the weld 3 is tight, and the laser beam 2 is welded along the weld 3.

[0046] S4: welding: placing the fixture for fixing the magnesium alloy substrate 1 to be welded on the workbench of the laser welding machine, setting the laser welding parameters, aligning the laser beam 2 with the weld 3, and welding, and cleaning with an ultrasonic cleaner and drying after processing;

[0047] Specifically, the laser welding parameters in step S4 are: laser power 800-1200W, welding speed 25-35mm / s, defocus 0-5mm, weld 3 is protected on both sides by argon gas, the front argon gas flow rate is 20-22.5L / min, and the back argon gas flow rate is the same as the front argon gas flow rate.

[0048] S5: Micro-arc oxidation: The prepared electrolyte is placed in a stainless steel tank, which serves as the cathode. The magnesium alloy plate after laser welding is also placed in the electrolyte as the anode. Then, a micro-arc oxidation power supply device is used for micro-arc oxidation treatment. After the treatment, it is rinsed with distilled water and blown dry.

[0049] Specifically, the power supply equipment for the micro-arc oxidation treatment in step S5 may preferably be a FL7-MAO30G micro-arc oxidation power supply equipment, and the temperature of the electrolyte during the micro-arc oxidation treatment is between 40-50°C.

[0050] Specifically, the electrolysis parameters in the micro-arc oxidation treatment in step S5 are: constant voltage mode, positive voltage 300V-500V, negative voltage 0V-30V, duty cycle 10-30%, power frequency 300-800Hz, oxidation time 5-30min.

[0051] The electrolyte is an aqueous solution composed of a uniform mixture of sodium silicate, sodium hydroxide, potassium fluorozirconate and deionized water.

[0052] Specifically, the preparation of the electrolyte in step S5 includes the following specific steps:

[0053] S51: First, place corresponding amounts of sodium silicate and sodium hydroxide in a beaker, stir magnetically, and fully dissolve;

[0054] S52: Place the corresponding amount of potassium fluorozirconate in another beaker, add deionized water to dissolve, heat to 50° C., stir magnetically, and fully dissolve;

[0055] S53: pouring the dissolved potassium fluorozirconate solution into the prepared sodium silicate and sodium hydroxide solutions, stirring sufficiently and reacting completely to obtain a milky white colloidal solution;

[0056] S54: diluting the prepared milky white colloidal solution to a corresponding electrolyte volume and pouring it into a stainless steel tank for use;

[0057] Among them, the mass ratio of sodium silicate, sodium hydroxide, potassium fluorozirconate and deionized water is 6:1:2:500.

[0058] Among them, potassium fluorozirconate undergoes the following chemical reaction with hydroxide ions under alkaline conditions due to hydrolysis:

[0059]

[0060]

[0061] During the reaction of micro-arc oxidation, due to the alkaline conditions of the electrolyte, the zirconium hydroxide colloidal particles reacted by the electrolyte mixture are negatively charged. Under the action of the electric field, the negatively charged zirconium hydroxide colloidal particles move from the cathode to the anode and adhere to the magnesium alloy weldment. Due to plasma discharge, under the action of high temperature and high pressure, the zirconium hydroxide colloidal particles decompose, accompanied by high-temperature molten oxides, gush out through the plasma discharge channel, and contact with the electrolyte at a lower temperature. Under the rapid cooling condition of the electrolyte, zirconium oxide nanoparticles are generated. Generally, during the reaction of micro-arc oxidation, defects such as thermal cracks and pores will be generated. However, since zirconium oxide nanoparticles participate in the reaction of micro-arc oxidation, such nanoparticles have the characteristics of phase change toughening. During the growth of the film layer, they can play the advantages of their volume phase change and inhibit the expansion of cracks in the micro-arc oxidation film layer. The zirconium oxide nanoparticles generated by the reaction can fill the micropores to a certain extent, increase the thickness of the film layer, and the zirconium hydroxide particles that are not completely decomposed in the process continue to be deposited on the surface of the micro-arc oxidation film layer under the action of the electric field, which plays a role in blocking defects such as pores and cracks.

[0062] Specifically, the micro-arc oxidation film formed in the micro-arc oxidation process contains nano-zirconium oxide phase particles.

[0063] Example 1 Obtaining Weld-MAO-Zr Products

[0064] Step 1: Wire cutting material

[0065] First, a 100mm×100mm×2mm magnesium alloy sheet AZ31B was cut into a 25mm×50mm×2mm size welding pattern using a wire cutting machine;

[0066] Step 2: Pretreatment to remove oxide film

[0067] The sample to be welded processed in step 1 is polished with SiC sandpaper from 400# to 2000# sandpaper in stages with a size of 25mm×50mm×2mm, rinsed with deionized water, ultrasonically cleaned and degreased in acetone solution, and then stored in bags;

[0068] Step 3: Assembly

[0069] Assemble the magnesium alloy sample to be welded saved in step 2 on the fixture, place the magnesium alloy sample to be welded on the upper surface of the fixture base 10, and the weld area at the joint, so that the weld 3 is flush with the open groove 111 of the protective gas channel 11 at the center line of the fixture base 10 to prevent the weld 3 on the back of the magnesium alloy from oxidizing, and the connecting rod 21 presses the magnesium alloy sample to be welded from above and is connected to the mounting groove 22 on the fixture base 10 with bolts;

[0070] Step 4: Welding

[0071] Place the fixture assembled in step 3 on the workbench of the laser welding machine, and set the laser welding parameters: laser power 1000W, welding speed 30mm / s, defocus 0mm, argon gas is introduced into the protective gas channel 11, and argon gas is used to protect both sides of the weld 3, the front argon flow rate is 22.5L / min, and the back argon flow rate is the same as the front argon flow rate. After welding the magnesium alloy sample to be welded, put it into acetone solution for ultrasonic cleaning;

[0072] Step 5: Micro-arc oxidation

[0073] First, prepare the electrolyte: 1) First, dissolve 12g of sodium silicate and 2g of sodium hydroxide in 500ml of deionized water, stir magnetically, and fully dissolve; 2) Add 4g of potassium fluorozirconate to 300ml of deionized water, heat to 50°C, stir magnetically, and fully dissolve the potassium fluorozirconate in the deionized water; 3) After the above operations are completed, in order to prevent potassium fluorozirconate from precipitating due to the decrease in temperature, the potassium fluorozirconate solution at the corresponding temperature is poured into the prepared sodium silicate and sodium hydroxide solutions, stirred fully and reacted completely, and the resulting milky white colloidal solution is fixed to 1L electrolyte capacity and poured into a stainless steel tank.

[0074] The magnesium alloy welding sample prepared in step 4 is placed in a stainless steel tank filled with electrolyte, with the stainless steel tank as cathode and the magnesium alloy laser welding sample as anode, and the FL7-MAO30G micro-arc oxidation power supply equipment is used for micro-arc oxidation treatment, using constant voltage mode, positive voltage 400V, negative voltage -30V, duty cycle 15%, power frequency 500Hz, oxidation time 10min. During the micro-arc oxidation process of the sample, the solution temperature is maintained at 40°C, and after the treatment, it is rinsed with distilled water and blown dry to obtain the Weld-MAO-Zr product.

[0075] Example 2 Obtaining weld-MAO products

[0076] Step 1: Wire cutting material

[0077] First, a 100mm×100mm×2mm magnesium alloy sheet AZ31B was cut into a 25mm×50mm×2mm size welding pattern using a wire cutting machine;

[0078] Step 2: Pretreatment to remove oxide film

[0079] The sample to be welded processed in step 1 is polished with SiC sandpaper from 400# to 2000# sandpaper in stages with a size of 25mm×50mm×2mm, rinsed with deionized water, ultrasonically cleaned and degreased in acetone solution, and then stored in bags;

[0080] Step 3: Assembly

[0081] Assemble the magnesium alloy sample to be welded saved in step 2 on the fixture, place the magnesium alloy sample to be welded on the upper surface of the fixture base 10, and the weld area at the joint, so that the weld 3 is flush with the open groove 111 of the protective gas channel 11 at the center line of the fixture base 10 to prevent oxidation of the weld on the back of the magnesium alloy, and the connecting rod 21 presses the magnesium alloy sample to be welded from above and is connected to the mounting groove 22 on the fixture base 10 with bolts;

[0082] Step 4: Welding

[0083] Place the fixture assembled in step 3 on the workbench of the laser welding machine, and set the laser welding parameters: laser power 1000W, welding speed 30mm / s, defocus 0mm, argon gas is introduced into the protective gas channel 11, and argon gas is used to protect both sides of the weld 3, the front argon flow rate is 22.5L / min, and the back argon flow rate is the same as the front argon flow rate. After welding the magnesium alloy sample to be welded, put it into acetone solution for ultrasonic cleaning;

[0084] Step 5: Micro-arc oxidation

[0085] First, prepare the electrolyte: put 12g of sodium silicate and 2g of sodium hydroxide into 1L of deionized water, stir evenly, and put it into a stainless steel tank.

[0086] The stainless steel tank was used as cathode and the magnesium alloy laser welding sample was used as anode. The FL7-MAO30G micro-arc oxidation power supply equipment was used for micro-arc oxidation treatment. The constant voltage mode was adopted, with a positive voltage of 400V, a negative voltage of -30V, a duty cycle of 15%, a power frequency of 500Hz, and an oxidation time of 10min. During the micro-arc oxidation process of the sample, the solution temperature was maintained at 40°C. After the treatment, it was rinsed with distilled water and blown dry to obtain the weld-MAO product.

[0087] Example 3 Obtaining Mg-weld products

[0088] Step 1: Wire cutting material

[0089] First, a 100mm×100mm×2mm magnesium alloy sheet AZ31B was cut into a 25mm×50mm×2mm size welding pattern using a wire cutting machine;

[0090] Step 2: Pretreatment to remove oxide film

[0091] The sample to be welded processed in step 1 is polished with SiC sandpaper from 400# to 2000# sandpaper in stages with a size of 25mm×50mm×2mm, rinsed with deionized water, ultrasonically cleaned and degreased in acetone solution, and then stored in bags;

[0092] Step 3: Assembly

[0093] Assemble the magnesium alloy sample to be welded saved in step 2 on the fixture, place the magnesium alloy sample to be welded on the upper surface of the fixture base 10, and the weld area at the joint, so that the weld 3 is flush with the open groove 111 of the protective gas channel 11 at the center line of the fixture base 10 to prevent oxidation of the weld on the back of the magnesium alloy, and the connecting rod 21 presses the magnesium alloy sample to be welded from above and is connected to the mounting groove 22 on the fixture base 10 with bolts;

[0094] Step 4: Welding

[0095] Place the fixture assembled in step 3 on the workbench of the laser welding machine, and set the laser welding parameters: laser power 1000W, welding speed 30mm / s, defocus 0mm, argon gas is introduced into the protective gas channel 11, and argon gas is used to protect both sides of the weld 3, the front argon flow rate is 22.5L / min, and the back argon flow rate is the same as the front argon flow rate. After welding the magnesium alloy sample to be welded, put it into acetone solution for ultrasonic cleaning, blow dry, and obtain the Mg-weld product.

[0096] Example 4 Testing of Corrosion Performance of Magnesium Alloy Welded Joints

[0097] The product of Example 3 was used as a control group. The magnesium alloy welded joint composite micro-arc oxidation samples prepared in the above examples and control examples were processed into joint area samples of 10×10×2 mm, and then encapsulated with epoxy resin and copper wire to form electrochemical samples. 3.5wt% sodium chloride solution was used as the corrosion medium, and electrochemical experiments were carried out under a three-electrode system.

[0098] Depend on Figure 2It can be seen that the corrosion resistance of the welded sample joint area treated by this method is good, and due to the addition of potassium fluorozirconate, its corrosion resistance is significantly improved. The self-corrosion current at Mg-Weld (Example 3) is 5.72×10 - 6 A / cm 2 The self-corrosion current of magnesium alloy welded joint after composite micro-arc oxidation treatment Weld-MAO (Example 2) is 2.40×10 - 7 A / cm 2 The self-corrosion current density of the magnesium alloy welded joint after the composite micro-arc oxidation treatment Weld-MAO-Zr (Example 1) after adding zirconate is 6.58×10 -8 A / cm 2 Compared with the self-corrosion current of Weld-MAO in Example 2 and the self-corrosion current of Mg-Weld manufactured in Example 3, the self-corrosion current density of Weld-MAO-Zr in Example 1 is reduced by one order of magnitude compared with that in Example 2 and by two orders of magnitude compared with that in Example 3.

[0099] Depend on Figure 3 It can be seen from the electrochemical impedance spectrum that the larger the semicircle radius of the impedance spectrum, the better the corrosion resistance under this condition. Therefore, the impedance spectrum of the magnesium alloy weld joint treated with composite micro-arc oxidation Weld-MAO-Zr (Example 1) after adding zirconate is larger in size, so its corrosion resistance is better, which is consistent with the results of the polarization curve diagram.

[0100] like Figure 4 , Figure 5 As shown, Figure 4 This is the SEM image of the magnesium alloy welded joint treated with Weld-MAO by composite micro-arc oxidation. Figure 5 The SEM image of the magnesium alloy welded joint treated with composite micro-arc oxidation Weld-MAO-Zr after adding zirconate. From the SEM image of the magnesium alloy welded joint treated with composite micro-arc oxidation Weld-MAO (Example 2), it can be seen that obvious cracks are generated in the joint film layer area and accompanied by large pores. However, from the SEM image of the magnesium alloy welded joint treated with composite micro-arc oxidation Weld-MAO-Zr (Example 1) after adding zirconate, it can be seen that the cracks in the joint film layer area have a significant trend of reduction, and the pores are reduced accordingly. Therefore, it is believed that the zirconium oxide nanoparticles and undecomposed zirconium hydroxide particles adhere to the film layer under the combined action of the electric field force to cover the pores and cracks.

[0101] The experimental results show that the corrosion resistance of the welded sample joint area treated by the method of the present application is good. In the SEM morphology of the magnesium alloy welded joint area, compared with the micro-arc oxidation sample without potassium fluorozirconate, the pores and cracks in the welded joint area have a better healing trend. Among them, the healing mechanism of cracks and pores is: during the reaction of micro-arc oxidation, due to the alkaline conditions of the electrolyte, the zirconium hydroxide colloidal particles reacted by the electrolyte mixing are negatively charged. Under the action of the electric field, the negatively charged zirconium hydroxide colloidal particles move from the cathode to the anode and adhere to the magnesium alloy welded parts. Due to plasma discharge, under the action of high temperature and high pressure, the zirconium hydroxide colloidal particles decompose, accompanied by high temperature molten oxides gushing out through the plasma discharge channel, and contacting with the electrolyte at a lower temperature, and generating zirconium oxide nanoparticles under the rapid cooling conditions of the electrolyte. In general, during the reaction of micro-arc oxidation, defects such as thermal cracks and pores will be generated. However, since zirconium oxide nanoparticles participate in the reaction of micro-arc oxidation, these nanoparticles have the characteristics of phase change toughening. During the growth of the film layer, they can play the advantages of their volume phase change and inhibit the expansion of cracks in the micro-arc oxidation film layer. The zirconium oxide nanoparticles produced by the reaction can fill the micropores to a certain extent, increase the thickness of the film layer, and the zirconium hydroxide particles that are not completely decomposed in the process continue to be deposited on the surface of the micro-arc oxidation film layer under the action of the electric field, which plays a role in blocking defects such as pores and cracks. Among them, zirconium oxide nanoparticles are produced by chemical reactions. Compared with artificially added zirconium oxide nanoparticles, their phase interface is relatively clean, and it is not easy to produce stress concentration due to the impurity of the interface, and cracks are preferentially generated at the phase interface. This method applies potassium fluorozirconate to the welded joint. Since there are fewer cracks at the joint, its corrosion resistance is significantly improved.

[0102] In summary, the technical solution of this application has the following beneficial effects:

[0103] 1. The present invention adopts micro-arc oxidation technology to produce zirconium oxide nanoparticles for magnesium alloy welded joint products, inhibits the expansion of film cracks, overcomes the defects of pores and thermal cracks generated in the conventional micro-arc oxidation process, and further improves the corrosion resistance of magnesium alloy laser welded joints.

[0104] 2. The present invention adopts the technology of micro-arc oxidation in an electrolyte added with potassium fluorozirconate. The micro-arc oxidation film layer generated on the surface of the magnesium alloy contains nano zirconium oxide phase particles, which is beneficial to improving the corrosion resistance of magnesium alloy laser welding joints. Zirconium oxide nanoparticles are produced by chemical reactions. Compared with artificially added zirconium oxide nanoparticles, their phase interface is relatively clean and not easy to produce stress concentration due to impurities in the interface. Cracks are preferentially generated at the phase interface. This method applies potassium fluorozirconate to the welded joint. Since there are fewer cracks at the joint, its corrosion resistance is significantly improved.

[0105] 3. During the welding process, the present invention sets a self-made fixture so that the weld is located at the opening of the protective gas channel, and argon gas is introduced into the protective gas channel to achieve double-sided flow of argon gas in the weld area, thereby preventing the magnesium alloy workpiece from being oxidized during the welding process and affecting the joint performance as much as possible.

[0106] The above are only preferred embodiments of the present invention, and are not intended to limit the implementation methods and protection scope of the present invention. Those skilled in the art should be aware that all solutions obtained by equivalent substitutions and obvious changes made using the description and illustrations of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for improving the corrosion resistance of magnesium alloy laser welded joints, characterized in that: The following steps are involved: S1: Wire cutting material: Use a wire cutting machine to cut the magnesium alloy sheet into the required size to form a flat magnesium alloy substrate to be welded; S2: Pretreatment: The cut magnesium alloy substrate is polished step by step with SiC sandpaper to remove the surface oxide film, and then cleaned and degreased, and then dried and bagged for storage; S3: Assembly before welding: Fix the pre-treated magnesium alloy substrate on the fixture to ensure that the weld is flush with the shielding gas channel on the fixture; S4: Welding: Place the fixture that fixes the magnesium alloy substrate to be welded on the workbench of the laser welding machine, set the laser welding parameters, align the laser beam with the weld, and weld. After processing, clean it with an ultrasonic cleaner and blow dry it; S5: Micro-arc oxidation: The prepared electrolyte is placed in a stainless steel tank, which serves as the cathode. The magnesium alloy plate after laser welding is also placed in the electrolyte as the anode. Then, a micro-arc oxidation power supply device is used for micro-arc oxidation treatment. After the treatment, it is rinsed with distilled water and blown dry. The electrolyte is an aqueous solution composed of a uniform mixture of sodium silicate, sodium hydroxide, potassium fluorozirconate and deionized water.

2. The method for improving the corrosion resistance of magnesium alloy laser welded joints according to claim 1, characterized in that: The clamp includes a clamp base and a fixing component. A groove-shaped protective gas channel is opened in the middle of the clamp base, and an open groove is opened in the protective gas channel at the center line of the clamp base; the fixing component includes a mounting groove and a connecting rod. The mounting grooves are horizontally arranged on both sides of the upper and lower ends of the opening groove, and longitudinal connecting rods are arranged on the left and right sides of the opening groove. The two ends of the connecting rod are respectively fixed on the mounting grooves on the upper and lower sides.

3. The method for improving the corrosion resistance of magnesium alloy laser welded joints according to claim 2, characterized in that: The step S3 specifically includes: the two magnesium alloy substrates to be welded are spliced ​​together at the welding position to form a weld, the weld is placed along the open groove so that the back of the weld is located at the opening of the protective gas channel, the magnesium alloy substrates on both sides of the weld are pressed and fixed by the connecting rod respectively, and the two ends of the connecting rod are fixed in the installation groove by bolts.

4. The method for improving the corrosion resistance of magnesium alloy laser welded joints according to claim 1, characterized in that: The step S2 also specifically includes: the SiC sandpaper step-by-step grinding is to use 400#-2000# sandpaper to grind step by step to remove the surface oxide film, the polished magnesium alloy substrate is rinsed with deionized water, then placed in an acetone solution to remove oil by ultrasonic cleaning, and then dried and stored in bags.

5. The method for improving the corrosion resistance of magnesium alloy laser welded joints according to claim 1, characterized in that: The laser welding parameters in step S4 are: laser power 800-1200W, welding speed 25-35mm / s, defocus 0-5mm, the weld is protected on both sides by argon gas, the front argon gas flow rate is 20-22.5L / min, and the back argon gas flow rate is the same as the front argon gas flow rate.

6. The method for improving the corrosion resistance of magnesium alloy laser welded joints according to claim 1, characterized in that: The electrolyte preparation in step S5 comprises the following specific steps: S51: First, place corresponding amounts of sodium silicate and sodium hydroxide in a beaker, stir magnetically, and fully dissolve; S52: Place the corresponding amount of potassium fluorozirconate in another beaker, add deionized water to dissolve, heat to 50° C., stir magnetically, and fully dissolve; S53: pouring the dissolved potassium fluorozirconate solution into the prepared sodium silicate and sodium hydroxide solutions, stirring sufficiently and reacting completely to obtain a milky white colloidal solution; S54: diluting the prepared milky white colloidal solution to a corresponding electrolyte volume and pouring it into a stainless steel tank for use; Among them, the mass ratio of sodium silicate, sodium hydroxide, potassium fluorozirconate and deionized water is 6:1:2:

500.

7. The method for improving the corrosion resistance of magnesium alloy laser welded joints according to claim 1, characterized in that: The electrolysis parameters in the micro-arc oxidation treatment in step S5 are: constant voltage mode, positive voltage 300V-500V, negative voltage 0V-30V, duty cycle 10-30%, power frequency 300-800Hz, oxidation time 5-30min.

8. The method for improving the corrosion resistance of magnesium alloy laser welded joints according to claim 1, characterized in that: The power supply equipment for the micro-arc oxidation treatment in step S5 is a FL7-MAO30G micro-arc oxidation power supply equipment.

9. The method for improving the corrosion resistance of magnesium alloy laser welded joints according to claim 1, characterized in that: The temperature of the electrolyte during the micro-arc oxidation treatment is between 40-50°C.

10. The method for improving the corrosion resistance of magnesium alloy laser welded joints according to claim 1, characterized in that: The micro-arc oxidation film layer formed in the micro-arc oxidation treatment process contains nano-zirconium oxide phase particles.

Citation Information

Patent Citations

  • Welding method for magnesium matrix composite

    CN102601527A

  • Electrolyte and plasma electrolytic oxidation process used for preparation of protection membrane of magnesium alloy laser welded joint surface

    CN104611749A

  • Magnesium alloy micro-arc oxidation ceramic membrane solution and ceramic membrane preparation method

    CN116288596A

  • Preparation method of ultralow-porosity magnesium alloy micro-arc oxidation corrosion-resistant and wear-resistant coating

    CN116607192A

  • Fusion zone purification by controlled laser welding

    US4000392A